Exploring miRNA-related Molecular Targets of Erchen Decoction against Lipid Metabolism Disorder using a Network Pharmacologic Approach - Ding, Shanshan; Chen, Qiliang; Huang, Yiqing; Li, Xiaomei; Chai, Yujuan; Li, Candong; Asakawa, Tetsuya (Combinatorial Chemistry & High Throughput Screening, 2022)
Background: Erchen Decoction (ECD) is a complex herbal formulation widely used for treating lipid metabolism disorder (LMD) in China. This study aims to explore the microRNA (miRNA)-related molecular targets of ECD against LMD using a network pharmacology approach (NPA) Methods: We randomly divided 20 male Sprague Dawley rats into two groups; 10 rats were normal controls, and the other 10 rats were fed a high-fat diet (HFD) for 12 weeks to establish an LMD model. Differentially expressed miRNAs (DE-miRs, HFD vs. Control) in the rats’ liver tissues were identified by miRNA sequencing and validated with qRT-PCR. Finally, the miRNArelated molecular targets for ECD activity against LMD were identified using a standard NPA by finding the intersection between identified DE-miRs-related targets and ECD-related targets. Result: We identified 8 DE-miRs and 968 targets and compared them to 262 ECD-related targets. A final list of 22 candidate targets was identified. Using a confidence score of >0.4, the network of (protein-protein interaction) PPI relationships exhibited 22 nodes and 67 edges. The GO and KEGG enrichment analyses revealed 171 molecular targets and 59 pathways, which were associated with ECD against LMD. Conclusion: The identified molecular targets and pathways suggest that complex mechanisms are involved in ECD’s mechanism of action, and immune-inflammation-related mechanisms are closely associated with the effects of ECD. The targets obtained in this study will guide future studies on the pharmacologic effects of ECD.
Keywords: microRNA